Envirobmentally safe method to process polyelemental fluorite ore - T. A. Oliinyk (Мінеральні ресурси України, 2025)
This study is devoted to processing of polyelemental fluorite ore of the Suschano-Perzhan zone of the Ukrainian Schield. The analysis of current trends in the involvement of rare earths metals in the processing of polyelemental ores. It is shown that the main direction of innovative activity is the development and application of methods for complex processing of mineral raw materials in order to obtain high-quality products and mining environmental risks at the same time. For this purpose, the technological properties of fluorite ore from the Central section of the Sushchano-Perzhan zone were investigated. The presence of rare elements (Y, Ga, Sr, Nb, Yb) in the ore up to 0.2% has been established, of which 50% fall to yttrium content. Fluorite is the main concentrator of yttrium (0.15%). The ore grinding flow consists of several seps, including, firstly, intensive destruction of aggregates with the release of quartz and feldspar grains, then further opening of mineral intergrowths, and finally decomposition of individualized mineral grains takes place. Since quartz and feldspars have higher strength than fluorite, the latter is re-ground, passing into the minus 0.044 mm class. It was found that the rate of opening of yttrium-fluorite grains obeys a polynomial law of the second degree with an approximation reliability of 0.9976. The rate of opening of feldspar and quartz grains (in sum) obeys a polynomial law of the third degree with an approximation reliability of 0.9737. For the first time for Sushchano-Perzhan zone, a technological process to separate fluorite from gangue minerals using anion flotation route was developed. Anionic reagents – crude tall oil soap and a new synthesized collector – talactum were used. Flotation experiments confirmed the complete depression of quartz and feldspar with the combined used of sodium silicate and aluminium sulfate. Economically significant fluorite concentrates with a mass fraction of fluorite of more than 90% were obtained with a CaF₂ extraction of 86.2–87.1% in the concentrate at a yield of 24.65–28.1%. The mass fraction of yttrium in the concentrate is 0.23%. This concentrate is recommended for smelting special steel grades or for extracting rare earth elements by plasma separation.